A Study on Effectiveness of Communication Skills in English among Higher Secondary Schools in Tiruvallur District - Paul, Anusha; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
English is a global language. The need to communicate in English is undeniable, however, English is an artificially acquired language in India. Especially due to the presence of vernacular medium of study or education. It has become a challenge in the communication skills of the higher secondary students who begin their career in the next years of education. Communication Skills in English provide a window of excellence for each and every student in higher education. As also provides an opportunity for career growth. The ability to communicate effectively provides an equal platform for the Indian students to excel en par with the international students. Although the Information Technology has revolutionalized English language learning, the medium is no substitute to a good teacher. The present study is confined to certain factors like Gender, Medium of Instruction, School Type, Class, Locality of School, Father’s Educational Qualifications, Mother’s Educational Qualification, Father’s Occupation, Mother’s Occupation, Socio-Economic status, Communiction in English and Interest in Language leraning. The Method of study adopted by the investigator is NORMATIVE SURVEY METHOD. The populace for the current study is the higher secondary school scholars studying in Tiruvallur districts in the State of Tamilnadu. The data was accumulated using questionnaires and Google forms. The present study constituted of 300 higher secondary students in various schools located in Tiruvallur district. The samples were collected using Simple Random Sampling Technique. How to cite this article: Paul A, Selvakumar YS. A Study on Effectiveness of Communication Skills in English among Higher Secondary Schools in Tiruvallur District. J Adv Res Eng & Edu 2022; 7(3): 9-12. DOI:  https://doi.org/10.24321/2456.4370.202206